Visual acuity after surgical management of ciliary body melanoma - Romanowska-Dixon, Bożena (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
The aim was to evaluate the visual acuity after transcleral resection of ciliary body melanoma. 42 patients were treated by trans-scleral resection of melanoma between January 1995 and June 2001. Additional rutenium brachytherapy was performed in 29 cases. Cataract surgery and intraocular lens implantation was necessary in 7 cases. Postoperative filtration bleb appeared in 6 eyes. The evaluation of functional results has shown no impairment of visual acuity in 56% of cases and did not change during follow up. These observations show that functional results after trans-scleral resection with additional brachytherapy are satisfactory and stable during follow-up.